2006
DOI: 10.1088/1126-6708/2006/12/066
|View full text |Cite
|
Sign up to set email alerts
|

Loop space, (2,0) theory, and solitonic strings

Abstract: We present an interacting action that lives in loop space, and we argue that this is a generalization of the theory for a free tensor multiplet. From this action we derive the Bogomolnyi equation corresponding to solitonic strings. Using the Hopf map, we find a correspondence between BPS strings and BPS monopoles in four-dimensional super Yang-Mills theory. This enable us to find explicit BPS saturated solitonic string solutions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…20) where we used D(Cẋ λ , ∇ λ H µνκ ) = 0 andẋ [ρẋσ] = 0. Equation(3.20) is simply the Bianchi identity for the field strengthF .…”
mentioning
confidence: 99%
“…20) where we used D(Cẋ λ , ∇ λ H µνκ ) = 0 andẋ [ρẋσ] = 0. Equation(3.20) is simply the Bianchi identity for the field strengthF .…”
mentioning
confidence: 99%
“…The on-shell supersymmetry variations for the components fields were obtained in [4]. It would be nice to see how to express this in terms of a superfield in a super loop space.…”
Section: N = (2 0) Supersymmetrymentioning
confidence: 99%
“…I am grateful to Urs Schreiber for having pointed this out to me. Another derivation can be found in[2,3,4].…”
mentioning
confidence: 99%
“…H * is a more general form of G 5 , chosen to have the analogous properties {H * , X i } = 0 and (H * ) 2 = 1. In fact using these properties (130) reduces to the simpler form…”
Section: A Generalized Basu-harvey Equationmentioning
confidence: 99%
“…The appearance of the deformation of the loop space by the presence of the background C field on the brane indicated that this may well be a way to view the five-brane. Ideas of this sort have been explored in [130,131] though as yet there is no clear theory of the five-brane. This article on M-theory is missing a key section on the Matrix models of M-theory [17].…”
Section: Other Ideasmentioning
confidence: 99%